UTILIZATION OF SPOT IMAGERY TO EVALUATE THE SUITABILITY OF RICE FIELD SPACE PATTERNS IN PADANG CITY - Ero Anelka Efendi; Dilla Angraina (Remote Sensing Technology Study Program, 2021)
that are converted into built-up lands such as housing, shops and industry. According to Darmawan (2002), one of the factors that cause land change is the socioeconomic factors of the community related to the needs of human life. One of the provinces that experienced the largest paddy land conversion in Indonesia is the West Sumatra region. Many factors result in land use changes that have an impact on the land itself, such as social, and economic factors and also factors of increasing the number of inhabitants. Land use change is the transition of an old form and location of land use to a new one. Or the change in the function of agricultural land such as built-up land (Adhiatma et al., 2020). The selection of the Padang City Area as a research site was based on significant land use changes in Padang City, this was caused by several factors such as the rate of population growth in Padang City which increased every year based on BPS data in 2015-2020 period was 1.52% with a population of 909.04 thousand people in 2020. The spatial pattern that has been set by the government in general in the city of Padang is an area developed for the cultivation of rice fields covering an area of 4540.10 ha. Based on BPS data from Padang City, the area of paddy fields decreases by 0.7% every year which is converted into housing and shops and industries in Padang City. The development of built-up land that occurred in the city of Padang slowly changed the rice field area into a built-up area that was not by the provisions of the spatial pattern that had been set by the local government. The spatial pattern that has been set by the government so that the area of paddy fields can be maintained by utilizing remote sensing data. By using remote sensing data such as imagery. Spot imagery is one of the high-resolution remote sensing images that is a French-owned satellite that operates to provide remote sensing data. SPOT imagery provides an imaging instrument that is then carried out as an overlay method between the rice field map and the rice field space pattern that has been set by the government to see its suitability. High-resolution optics are synonymous with panchromatic (P) and Multispectral (Green, Red, and Near Infrared). SPOT imagery has a spatial resolution of 2.5meter 10meters with a wide viewing angle that covers 60 x 60 km or 60 x 120 km in twin mode instruments, and an orbital altitude of 822 km, SPOT provides an ideal combination of high resolution and also wide visibility that can meet the needs of data that is accurate enough for identification of rice fields.